2016
DOI: 10.1182/blood-2015-10-636480
|View full text |Cite
|
Sign up to set email alerts
|

Acquired von Willebrand syndrome associated with left ventricular assist device

Abstract: Left ventricular assist devices (LVAD) provide cardiac support for patients with end-stage heart disease as either bridge or destination therapy, and have significantly improved the survival of these patients. Whereas earlier models were designed to mimic the human heart by producing a pulsatile flow in parallel with the patient’s heart, newer devices, which are smaller and more durable, provide continuous blood flow along an axial path using an internal rotor in the blood. However, device-related hemostatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
150
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(158 citation statements)
references
References 124 publications
6
150
0
2
Order By: Relevance
“…Circulatory assistance devices such as LVADs can also cause loss of HMWM and result in bleeding and angiodysplasia. LVAD bleeding is similar to that observed in Heyde’s syndrome 100,101. In many cases, both VWF:RCo and VWF:Ag levels remain normal 100,102,103.…”
Section: Acquired Vws and Left Ventricular Assist Devices (Lvads)supporting
confidence: 72%
“…Circulatory assistance devices such as LVADs can also cause loss of HMWM and result in bleeding and angiodysplasia. LVAD bleeding is similar to that observed in Heyde’s syndrome 100,101. In many cases, both VWF:RCo and VWF:Ag levels remain normal 100,102,103.…”
Section: Acquired Vws and Left Ventricular Assist Devices (Lvads)supporting
confidence: 72%
“…This may have resulted in greater shear stress and exacerbated von Willebrand factor deficiency. 24 Further investigation into this association may shed more light on the mechanism of increased bleeding risk in obese patients. The present study had several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…27 In addition, more recent data have demonstrated that AVWS is also common in patients with cardiovascular disorders including aortic valve stenosis and those treated with left ventricular assist devices. 28 Management of bleeding complications in AVWS frequently poses a major clinical challenge. Although DDAVP and VWF-containing concentrates can be useful in transiently increasing plasma VWF levels, markedly enhanced clearance of VWF and FVIII in AVWS limits the efficacy of these agents.…”
Section: Clinical Management Of Bleeding Episodes and Adjunctive Thermentioning
confidence: 99%